DETEKSI JUMLAH BAKTERI PADA DAUN SELADA YANG BERASAL DARI PASAR RAYA,PASAR GAUNG,DAN PASAR PAGI LOLONG - Aissa Febrya, Malika; Advinda, Linda (Jurnal Biogenerasi, 2025)
Vegetables are rich in vitamins and minerals and are generally widely consumed by the public. One popular type of vegetable is lettuce because of its attractive texture and color. The cleanliness of vegetables is very important to prevent diseases caused by food contaminated with pathogenic bacteria. In this study, the number of bacteria on lettuce leaves in three different markets in Padang city was tested. The method used was the laboratory observation method by diluting with 3 repetitions. The results showed that the number of bacterial colonies on lettuce in Pasar Raya was 93 colonies, in Pasar Gaung was 61 colonies, and in Pasar Pagi Lolong was 69 colonies. The placement of vegetables in Gaung Market which has a special row for vegetables can maintain the cleanliness of vegetables, while in Raya Market and Lolong Market there is no special placement for vegetables so that vegetables are vulnerable to contamination with other materials. Bacterial contamination of vegetables can come from various factors such as the planting process, spraying organic fertilizer, harvesting, and washing. Therefore, it is necessary to pay attention to hygiene and sanitation in processing and selling vegetables to prevent bacterial contamination.